1978
DOI: 10.1007/bf02430670
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal exchange processes in sediment-water systems

Abstract: / Experimental data for sorption of Hg, Cd, Cu, and Pb by sand, silt, and organic-rich sediments from the Ottawa River, Canada show significant conformity to Langmuir's equation. Values of the bonding energy constant and the sorption maximum correlate directly with organic content and mean grain size (q~). Desorption experiments indicate that the heavy metals form stable complexes in nitrilotriacetate (NTA) and NaCI Solutions, with the following desorption ratios: Hg, 1:1 (CI-:NTA); Pb, 1:10; Cd, 1:2. Serial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 16 publications
0
18
0
5
Order By: Relevance
“…Fine-grained top layers of stream sediments have been used to study metal contamination in the vicinity of landfills, since metals generally accumulate on smaller grain fractions of sediment because of the higher surface area-to-grain size ratio (Gibbs, 1973;Harding and Brown, 1978;Ramamoorthy and Rust, 1978;Sinex and Helz, 1981;Rule, 1986;Yanful et al, 1988;Mantei and Coonrod 1989). Therefore, the mineralogy of the material used in the landfill controls the possibility of pollutant escape in the environment (Hermanns Stengele and Plötze, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Fine-grained top layers of stream sediments have been used to study metal contamination in the vicinity of landfills, since metals generally accumulate on smaller grain fractions of sediment because of the higher surface area-to-grain size ratio (Gibbs, 1973;Harding and Brown, 1978;Ramamoorthy and Rust, 1978;Sinex and Helz, 1981;Rule, 1986;Yanful et al, 1988;Mantei and Coonrod 1989). Therefore, the mineralogy of the material used in the landfill controls the possibility of pollutant escape in the environment (Hermanns Stengele and Plötze, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements As, Cu, Zn and Pb showed elevated concentrations in the stream sediments. Enrichment of metals in stream sediments caused by various contamination sources have been reported (Ramamoorthy andRust, 1978, Rule, 1986). Studies have shown elevated concentrations of Cu, Pb, Zn, Cd, Ag, and Ba in stream sediments affected by landfills and water treatment facilities Coonrod 1989, Mantei andFoster 1991).…”
Section: XLVII No 2 -976mentioning
confidence: 99%
“…Concomitantly, the equilibria of carbonate and hydroxide complexes are controlled by pH (Ramamoorthy 1978). Calcium, magnesium and iron can also compete with trace metals for humic and fulvic acids.…”
Section: Watershed Characteristicsmentioning
confidence: 99%